Arbuscular mycorrhizal fungi and proximal sensing for improving nutrient use efficiencies in wheat (Triticum aestivum L.). (28th May 2022) - Varinderpal-Singh,; Kunal,; Gosal, Satwant Kaur; Choudhary, Rita; Singh, Reena; Adholeya, Alok
Abstract: A 4 years field study was conducted to improve nitrogen (N) and phosphorus (P) use efficiencies in wheat ( Triticum aestivum L.) using arbuscular mycorrhizal fungi (AMF) and precision N management. Split plot design was employed to rationalize N and P fertilizer use in two different experiments with AMF in the main plot and fertilizer application practice in the subplots. The AMF seed coating improved mycorrhization, root dry weight and P uptake. AMF coating of wheat seeds improved mean grain yield and agronomic efficiency of applied P fertilizer (AEP ) by 11% and 55.4%, respectively. However, AMF seed coating did not improve chlorophyll content, normalized difference vegetative index, grain yield and agronomic efficiency of applied N fertilizer (AEN ). Precision N management using leaf color chart (LCC), chlorophyll meter (SPAD), and GreenSeeker optical sensor (GS) sustained wheat grain yield equivalent to the soil-test based N fertilizer recommendation with 20–31 kg ha −1 less fertilizer N. Proximal sensing guided N use improved AEN by 21.9%–39.6% while mitigating global warming potential by 16%–24%. Integrated use of AMF seed coating and precision N management provides a potential solution to improve N and P nutrition and reduce environmental footprints of fertilizer N use in wheat.